2011
DOI: 10.2174/092986711795656216
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Strategies Effective Against Infectious Bacterial Biofilms

Abstract: Bacteria are able to adapt to undesirable changes in nutrient availability, environmental conditions and presence of antimicrobial products, as well as to immunological defenses. One particularly important example of bacterial adaptation is the ability to grow as part of a sessile community, commonly referred to as biofilm. It is a natural tendency of microorganisms to attach to biotic or abiotic surfaces, to multiply and to embed themselves in a slimy matrix, resulting in biofilms. Biofilms are the leading ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
75
0
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(82 citation statements)
references
References 169 publications
(234 reference statements)
2
75
0
5
Order By: Relevance
“…It was found that both products disrupted the structure and viability of biofilm cells. The association between biofilm formation and antimicrobial resistance remains to be a serious health issue in the current days (Simões 2011), which encourages the search for active molecules able to disrupt biofilm integrity. Hence, the harmful effects of the extract/fraction upon biofilm assembly seen in this study could contribute to render the biofilm more susceptible to other antifungal drugs.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that both products disrupted the structure and viability of biofilm cells. The association between biofilm formation and antimicrobial resistance remains to be a serious health issue in the current days (Simões 2011), which encourages the search for active molecules able to disrupt biofilm integrity. Hence, the harmful effects of the extract/fraction upon biofilm assembly seen in this study could contribute to render the biofilm more susceptible to other antifungal drugs.…”
Section: Discussionmentioning
confidence: 99%
“…This fully justifies current research aimed at the development of therapeutic strategies that target biofilm formation and dispersal (Simões, 2011). Current management practices for P. aeruginosa infections include hygienic measures (Høiby & Pedersen, 1989), early aggressive eradication by antimicrobial therapy (Döring & Høiby, 2004), the use of nebulized DNAse (Frederiksen et al, 2006) and chronic suppressive antibiotic therapy (Bjarnsholt et al, 2009;Döring et al, 2000).…”
Section: Modulation Of Biofilm-forming Microbial Communitiesmentioning
confidence: 92%
“…From the moment that cells are under the protection of biofilm, they become resistant to antibiotics and to immune responses, which increase the difficulties for the clinical treatment of biofilm infections. It has been reported that bacteria in biofilms have a greater resistance to antimicrobial stress than their planktonic counterparts and the antimicrobial concentrations necessary to inhibit bacterial biofilms can be up to 10-1000 times higher than those needed to inhibit the same bacteria grown planktonically [4][5][6]. Strategies for biofilm-associated infections include: removal of the foreign bodies, prevention of initial contamination, minimization of microbial cell attachment, use of antimicrobials to penetrate the biofilm matrix and inactivate the embedded microorganisms [5].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that bacteria in biofilms have a greater resistance to antimicrobial stress than their planktonic counterparts and the antimicrobial concentrations necessary to inhibit bacterial biofilms can be up to 10-1000 times higher than those needed to inhibit the same bacteria grown planktonically [4][5][6]. Strategies for biofilm-associated infections include: removal of the foreign bodies, prevention of initial contamination, minimization of microbial cell attachment, use of antimicrobials to penetrate the biofilm matrix and inactivate the embedded microorganisms [5]. One of the significant advantages of a rapid bactericidal action may be that it permits wound healing to proceed without bacterial interference and reduces the likelihood for resistance to develop [7].…”
Section: Introductionmentioning
confidence: 99%